PENGARUH PERTUMBUHAN UMKM TERHADAP TINGKAT PENGANGGURANDI JAKARTA PUSAT PADA USAHA “MIE GACOAN” - Egen Ganesa; Agnes Catur Putri, Evi Nashriyah, Hilwa Ashfiya (CV. Adiba Aisha Amira, 2024)
Indonesia has an employment problem with a high unemployment rate. MSMEs an important role in raising incomes and adding new jobs. MSMEs can employ above 99.45% of the labor force and contribute about 30% to GDP. The purpose of this study is to look deeply into the role and contribution of MSMEs to the unemployment rate at Cempaka Putih, Central Jakarta. This study uses a quantitative approach, taking 92 respondents for data analysis. MSME's Growth (X) and The Unemployment Rate (Y) have a significant relationship, as seen from the correlation test results obtained R = 0.649. Determination coefficient tests the impact is 56.6% of ESME's growth variables on unemployment rate declines. However, 43,4% is an outside factor affecting the unemployment rate. At t-test get tcount > ttable or 8,088 > 1,980. It suggests a relation between MSME’s growth and the unemployment rate, or H0 rejected and H1 accepted